Wisatawan Flashpacker: Sebuah Pendekatan Epistemologis - Putu Diah Sastri Pitanatri (Magister Tourism Study, Faculty of Tourism, Udayana University, 2020)
This paper examines flashpacker as an area of research; which discusses the new phenomenon of the flashpacker originating it’s term from “backpacker”. In this review, a deeper analysis of the evolution and development is presented, charting the growth of the literature, focusing both chronology and epistemology. A framework for understanding and creating knowledge about flashpacker is presented, forming the basis which signposts established research themes and concepts and outlines some future directions for research. In addition, this article focuses on constraining and propelling forces, ontological advances, contributions from key journals, emerging themes and issues. The paper suggests that flashpacker has numerous foundational origins that have complicated its growth as a viable and valued concept. This paper also proposes a number of research activities in understanding the flashpacker. Keywords: flashpacker, epistemology, framework, creating knowledge, research activities